Hepatitis C virus drives increased type I interferon-associated impairments associated with fibrosis severity in antiretroviral treatment-treated HIV-1–hepatitis C virus-coinfected individuals. (1st June 2017) - Griesbeck, Morgane; Valantin, Marc-Antoine; Lacombe, Karine; Samri-Hassimi, Assia; Bottero, Julie; Blanc, Catherine; Sbihi, Zineb; Zoorob, Rima; Katlama, Christine; Guiguet, Marguerite; Altfeld, Marcus; Autran, Brigitte
Abstract : Background: Viral coinfections might contribute to the increased immune activation and inflammation that persist in antiretroviral treatment (ART)-treated HIV-1 patients. We investigated whether the hepatitis C virus (HCV) coinfection contributes to such alterations by impairing the plasmacytoid dendritic cell (pDC) IFNα/TLR7 pathway in a highly homogeneous group of ART-treated HIV-1–HCV-coinfected patients. Methods: Twenty-nine HIV-1-infected patients with fully suppressive ART were included, 15 of whom being HCV-coinfected with mild-to-moderate fibrosis and matched for their HIV-1 disease, and 13 control healthy donors. Cellular activation, plasma levels of inflammatory cytokines and pDC transcriptome associated with IFNα/TLR7 pathway were characterized. Results: Higher plasma levels of type-I interferon (IFN)-associated cytokines [interferon gamma-induced protein 10 (IP-10), MIP-1β, IL-8 and IFN-inducible T-cell alpha chemoattractant) were observed in HIV-1–HCV-coinfected than in HIV-1-monoinfected patients ( P = 0.0007, 0.028, 0.028 and 0.035, respectively). The pDCs and T cells displayed a more exhausted (LAG-3+ and CD57+, respectively) phenotype. The pDC IFNα pathway (defined by phosphorylated STAT1 expression) was constitutively activated in all patients, irrespective of HCV coinfection. Expression of interferon-stimulated genes (ISGs) EI2AK2, ISG15, Mx1 and IFI44 was increased in pDCs from HIV-1–HCV-coinfected individuals and was correlated with fibrosis score (Fibroscan, www.echosens.com, Paris, France and aspartate-aminotransferase/platelet-ratio index score, P = 0.026 and 0.019, respectively). Plasma levels of IP-10, STAT1 expression in pDCs and Mx1 mRNA levels in pDCs decreased after interferon-free anti-HCV treatment. Conclusion: HCV replication appears to drive increases in type-I IFN-associated inflammation and ISGs expression in pDCs, in association with fibrosis severity in ART-treated HIV-1-infected patients with mild-to-moderate fibrosis. Preliminary results indicate reduction of these alterations with earlier interferon-free anti-HCV treatment in those patients. Abstract : Supplemental Digital Content is available in the text